A comprehensive study of metabolite genetics reveals strong pleiotropy and heterogeneity across time and context - Apolline Gallois (Nature Portfolio, 2019)
Genome-wide association studies of metabolites have revealed hundreds of genetic associations using univariate analyses. Here, the authors use a multivariate approach to perform association analyses for 158 serum metabolites, followed by fine mapping and GxE interaction tests with statin use and age.